PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN DENGAN KINERJA KEUANGAN SEBAGAI VARIABEL INTERVENING (Studi Kasus Pada Perusahaan Manufaktur Sektor Barang - Fatimah Fatimah; Ronny Malavia Mardani; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACTThe purpose of this study is to find out how the influence of good corporate governance proxied managerial ownership on firm value with financial performance as an intervening variable. This research is a type of quantitative research. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2015-1017 period. Samples were selected using non-purposive sampling. The results of the study show that good corporate governance has a significant positive effect on firm value. Good corporate governance has a significant positive effect on financial performance. Financial performance has a significant influence on company value. While good corporate governance has a significant indirect effect on firm value by using financial performance as an intervening variable.Keywords: Good Corporate Governance, Company Value, and Financial Performance.